2003
DOI: 10.1029/2003jd003694
|View full text |Cite
|
Sign up to set email alerts
|

Cutoff and reestablishment of current in rocket‐triggered lightning

Abstract: .[1] A total of three negative rocket-triggered lightning flashes without return strokes (two from 1997 and one from 1993) are analyzed in this paper in order to study the processes associated with the disintegration of the triggering wire and its replacement by an airplasma channel. It appears that the gap resulting from the vaporization of the triggering wire by the upward-positive leader current is bridged by a leader/return-stroke type process. Electric fields at distances of 50, 110, and 500 m, the corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
47
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 37 publications
11
47
2
Order By: Relevance
“…Flash UF‐0707, a rocket‐and‐wire triggered flash, was initiated on 31 July 2007 at approximately 19:36 UT. This flash consisted of an initial stage (as in all negative triggered lightning flashes, involving an upward positive leader, destruction of the triggering wire, its replacement with a plasma channel, and subsequent steady current flow between cloud and ground [e.g., Rakov et al , 2003]) followed by two leader/return‐stroke sequences, with each stroke terminating to the launcher mounted on the top of an 11 m tower. The focus in this section is the first of these two strokes.…”
Section: Data and Analysismentioning
confidence: 99%
“…Flash UF‐0707, a rocket‐and‐wire triggered flash, was initiated on 31 July 2007 at approximately 19:36 UT. This flash consisted of an initial stage (as in all negative triggered lightning flashes, involving an upward positive leader, destruction of the triggering wire, its replacement with a plasma channel, and subsequent steady current flow between cloud and ground [e.g., Rakov et al , 2003]) followed by two leader/return‐stroke sequences, with each stroke terminating to the launcher mounted on the top of an 11 m tower. The focus in this section is the first of these two strokes.…”
Section: Data and Analysismentioning
confidence: 99%
“… Shao et al [1995, p. 2780] classify M components into early and late‐type M events. The early type are “those which are produced by positive streamer–fast negative recoil sequences immediately following return strokes,” and the late type are “those produced by negative breakdown into the channel, later in a continuing current.” Rakov and Uman [2003, p. 181] suggest that the two types “may differ only in the way in which the negative charge source is connected to the conducting channel to ground, not in the processes occurring in that channel.” Rakov et al [2001] show that M components transfer negative charge to ground and consist of a superposition of a downward incident wave and an upward reflected wave with nearly equal current amplitudes. The waves are guided by the preexisting conducting channel.…”
Section: Introductionmentioning
confidence: 99%
“…A summary of research on pulses and currents in lightning flashes can be found in the book by Rakov and Uman [2003, chapters 4 and 7]. For more recent results and reviews on triggered flashes and flashes to towers see the articles by Rakov et al [2003], Miki et al [2005], Campos et al [2007], Flache et al [2008], Campos et al [2009], Akita et al [2010], and Qie et al [2011].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the wire enhances the electric field produced by the cloud charge source. If the conditions are right, an electric discharge (known as a leader) propagates upward from the top of the wire, resulting in a flow of current in the wire, and when this current is sufficiently high (about 100 amperes) for a sufficient period of time (some milliseconds), the wire explodes and is replaced by a conducting plasma channel [ Rakov et al , 2003]. Following this process, a steady current of a few hundred amperes (known as the initial continuous current or ICC) flows to ground for several hundred milliseconds.…”
Section: Introductionmentioning
confidence: 99%